Effect of earthworm Eisenia fetida epidermal mucus on the vitality and pathogenicity of Beauveria bassiana - Xibei Zhou (Nature Portfolio, 2021)
Abstract Beauveria bassiana is one of the most widely studied and used entomopathogenic fungus as biopesticide. In the biological control of pests, B. bassiana will persist in the soil after application, and will inevitably contact with earthworms, especially the epigeic earthworm species. So, what are the effects of earthworm and its epidermal mucus on the activity of B. bassiana? We employed the epigeic earthworm Eisenia fetida, B. bassiana TST05 strain, and the insect Atrijuglans hetaohei mature larvae to study the impact of earthworm epidermal mucus on the vitality and pathogenicity of B. bassiana to insect. Methods included scanning electron microscope observation, detection of spore germination, fungal extracellular enzyme activity, and infection testing to A. hetaohei. The results showed that the B. bassiana spores may attach to the cuticle of E. fetida but they could be covered by the epidermal mucus and became rough and shrunken. After treatment with the epidermal mucus, the spore germination and extracellular enzymes of B. bassiana was significantly inhibited. Inoculation of A. hetaohei larvae with a mixture of B. bassiana and mucus showed that the mucus could reduce the pathogenicity of B. bassiana to the insect, resulting in a slower disease course and lower mortality. It was concluded that the epidermal mucus of the earthworm E. fetida can inhibit the activity of B. bassiana, as well as the infectivity and pathogenicity of fungus to target insects. However, after treatment with epidermal mucus the surviving B. bassiana still had certain infectivity to insects. This is of great significance for the application of B. bassiana in biological control of pests.